Resistance of Railway Vehicles to Derailment on Twisted Track - DING Xue-ping; LUO Yun (机车电传动)
Method of measuring the safety against derailment by running through a twisted test track in AS 7509.1"Railway Rolling Stock-Dynamic Behavior-Part 1: Locomotive Rolling Stock", which published in 2009 in Australia, was briefly introduced in this thesis. The safety against derailment was calculated based on the standard testing track condition in AS 7509.1 reappeared in the SIMPACK software. Compared with methods of computer simulation of vehicle resistance to flange climbing derailment at low speed in BS EN 14363 "Railway applications-Testing for the acceptance of running characteristics of railway vehicles -Testing of running behavior and stationary tests" published in 2005 in Europe, the AS 7509.1 standard is more reliable and applicable in the evaluation methods of railway vehicle resistance to derailment on twisted track.